The making of biblical womanhood: how the subjugation of women became gospel truth - Barr, Beth Allison (Brazos Press, 2021)
A trusted historian shows that "biblical womanhood" isn't biblical but arose from a series of clearly definable historical moments, and presents a better way forward for the contemporary church.